Profile of Junior High School Students’ Symbol Sense Thinking - Mutammam, Muhamad Badrul; Wulandari, Evi Novita (Universitas Muhammadiyah Mataram, 2023)
Algebra is one of the mathematics materials in junior high school which is synonymous with symbols. There is a concept to assess students' sensitivity to symbols, namely symbol sense. One of the skills that must be possessed by students is thinking skills. The purpose of this study is to describe the thinking process of junior high school students from the symbol sense task. This is qualitative research. The steps in this research is (1) making instruments; (2) selecting subjects; (3) collecting data; and (4) analyzing data.The subjects in the study consisted of four ninth-grade students who had good math and communication skills. Data collection was carried out by giving symbols of sense assignments and followed by task-based interviews. The collected data was then analyzed using the stages of data collection, data condensation, data display, and drawing conclusions. The results showed that all subjects showed good thinking skills. It's just that a student is not good at drawing conclusions because he does not check the answers independently. For the ability of the sense of symbol students lack achievement in two characteristics of the symbol sense. Only two people demonstrated the